Beyond you and I: role play and reflection-in-action in communication training. Issue 1 (2nd January 2017) - Fryer, Nic; Boot, Michelle
ABSTRACT: This article will explore the development of communication training within nurse training. Beginning by outlining current thinking around this practice, it then discusses Schön's notion of reflective practice and its frequently cited relevance to nursing before pointing out some of its limitations. In particular, it looks at the limitations of the individual being able to critically reflect on their self within a broader social context. Drawing on the theories of Habermas and Bourdieu, it suggests that encouraging a greater awareness of one's own social context, and hence of one's own subject position, would develop a deeper awareness of other potential perspectives and a better ability to listen to patients. Finally, it argues for the use of role play in assisting nurses to gain such awareness, particularly in difficult clinical situations such as end-of-life care.